Relationship between Workload Performance and Job Satisfaction - Asma Safdar; Fransisca Sri Susilaningsih; Titis Kurniawan (Jurnal Keperawatan Padjadjaran, 2019)
In Pakistan’s public health care delivery system, charge nurses hold a very challenging position to perform their workload. They have to work very hard to accomplish nursing and non-nursing care tasks which are imposed on them by the system. Overstretching of workload deprives them from concentration which is badly needed for their performance and this creates dissatisfaction which negatively impact on the quality of nursing care. As a result, this study intends to analyses the relationship between workload performance (WLP) and job satisfaction (JS). This correlation study involved 105 charge nurses in Nishtar Medical College and Hospital Multan Pakistan recruited by convenience sampling. Nurses’ WLP were collected by using self-developed instrument, and JS were collected by using modified Spector 1985. The collected data were analyze descriptively (mean, SD, frequencies, percentage) and inferentially (Pearson’s correlation). The results suggested that nurses’ WLP (average time consumption) in the morning (93.83%) and evening shift (95.63%) were higher compared with night shift (70.69%). Additionally, the proportion of time consumed in the morning and evening shift were higher on nursing care activities (Morning = 57.10%, Evening =52.1%) rather than non-nursing care activities. Oppositely, in the night shifts nurses consumed more than half of their time in non-nursing care activities (55. 66%). Charge nurses observed on moderate level of job satisfaction (mean = 38.6, SD = 5.42). There was no statistically significant correlation between nurses’ job satisfaction and workload performance (p =.137). The findings conclude nurses’ high workload and moderate level of job satisfaction and no statistically significant correlation between both. The results suggested that, it is important for hospital management to adopt some better strategies in order to improve WLP and JS.